Million People March Against Pork Barrel: From Potentiality to Actuality - Viray, Kriztine (Social Sciences and Development Review, 2016)
In this essay, I endeavor to ask how virtual reality becomes a public space for advocacies and a venue for crowd mobilization in the Philippines. I particularly analyze the Million People March (MPM) against pork barrel, which happened on August 26, 2013 at Luneta Park in Manila. I also discuss how micro-blogging sites (facebook and twitter) on the cyberspace stirred up the event even before becoming a physical and material event. I try to use the concepts of public sphere introduced by Jurgen Habermas (1989) and as expanded by Lincoln Dahlberg (2007) as cyberpublic, and as virtuality by Hayles and Deleuze (as quoted in A. de Souza e Silva & Sutko, 2011). I also discuss the limitations and constraints to the participative and democratic potentials of blogosphere as explained by Cammaerst (2008).